Orbital Period Changes of Selected Two Semi-Deteached Binaries - Muhammed Faruk Yıldırım (Journal of Advanced Research in Natural and Applied Sciences)
Since the data obtained from satellite data are very sensitive, the minima times of the target systems have obtained from Kepler (K2) and TESS observations. A total of 14 minima times were obtained from Kepler (K2) data for the AF Gem system and 11 minima times in two different sectors from the TESS data for the RY Gem system. In this study, orbital period behaviors of semi-detached binaries (SDBs) AF Gem and RY Gem systems have investigated, together with minima times obtained from literature and satellite data. It has been observed that the orbital periods of AF Gem and RY Gem decrease. The period change rates of AF Gem and RY Gem systems are determined as -4.1×10-8 and -6.5×10-6 day/ year. The magnetic activity of the cooler components of the systems may be the reason for the periods decrease, and therefore the mass loss rates of the systems have calculated. For AF Gem and RY Gem, mass loss rate was found to be -4.4×10-8 M⊙/year and -8.2×10-7 M⊙/year, respectively. In the O-C graph of AF Gem, sinüsoidal variations also exist. Sinusoidal change may be demonstrated as being the result of a light time effect (LITE) via a tertiary body around the eclipsing pair. The minimum mass of probable third star around AF Gem has found to be 0.24 M⊙.